A summary of the molecular testing recommended in acute myeloid leukemia - Ruth Stuckey; Cristina Bilbao-Sieyro; María Teresa Gómez-Casares (Annals of Molecular and Genetic Medicine - Peertechz Publications, 2020)
Advances in Next-Generation Sequencing technologies (NGS) are revealing germline and somatic mutations that, together with karyotype, determine the diagnosis and subtype of Acute Myeloid Leukemia (AML). Molecular testing is also essential for the genetic risk stratification of patients with AML, in particular for those with normal karyotype AML (CN-AML), a large and highly heterogeneous group of patients. Patients determined to be at high risk could benefit from a more aggressive first-line therapy, or a more directed therapy, such as midostaurin (for FLT3-mutated AML) or ivosidenib (for IDH1-mutated AML). Here, we will summarize the molecular testing currently recommended in AML and introduce new mutations that may have prognostic value and clinical application in the near future.